Diagnostic Evaluation of Polycystic Ovarian Disease - Nadia Ashraf, Aasma Hanif, Saima Rafique, Maria Ashfaq, Memoona Faiyaz (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Polycystic ovary syndrome is a heterogeneous endocrine disorder that affects about one in 15 females worldwide. The major endocrine disruption is excessive androgen secretion or activity, and a large proportion of women also have abnormal insulin activity. Many body systems are affected, resulting in several health complications, including menstrual dysfunction, infertility, hirsutism, acne, obesity, and metabolic syndrome. Several biochemical tests play an important role in diagnosing and predicting health consequences of this disease. Aims: To determine the signs and symptoms of polycystic ovarian syndrome in gynaecology outpatient department of Jinnah Hospital Lahore and to describe the clinical presentations, biochemical findings and ultrasound findings in patients with polycystic ovarian syndrome. Design Descriptive case series Setting: Department of Obstetrics & Gynecology, Jinnah Hospital Lahore from 1st March 2018 to 28th February 2019. Methodology: One hundred patients of reproductive age group with signs and symptoms of polycystic ovarian syndrome were included. A detailed history and examination was carried out. Then diagnosis of polycystic ovarian syndrome was confirmed by laboratory tests and ultrasound findings. Results: 72% patients presented with menstrual irregularities.56% patients had BMI> 25kg/m2 .72% patients had hirsutism. Out of total patients 62% patients were married and 38% were unmarried. Among those who were married 24(38.7%) patients presented with primary infertility and 17(27.4%) presented with secondary infertility.44% patients had raised total serum testosterone. Diabetes mellitus was present in 14% of patients. Ultrasound criteria were fulfilled in 77% patients with polycystic ovarian disease. Conclusion: Most common clinical presentations of polycystic ovarian disease were found to be menstrual irregularities, hirsutism and obesity. Hyperinsulinemia and hyperandrogenism was also more commonly found in obese XIV and hirsute women. Also ultrasound is a very useful diagnostic tool for polycystic ovarian disease.